Aristotle’s Refutation of the Eleatic Argument in Physics I.8 - Oki, Takashi (Peitho. Examina Antiqua, 2021)
In this paper, I show that Aristotle’s refutation of the Eleatic argument in Physics I.8 is based on the idea that a thing at the starting point of coming to be is composite and is made up of what underlies and a privation. In doing so, I clarify how the concept of accidentality as used in his solution should be understood in relation to the composite nature of what comes to be. I also suggest an explanation of why Aristotle’s discussion of the Eleatic dilemma in Physics I.8, unlike his discussion in the previous chapter, is not clear.